Optimization of The Application of The Covid 19 Health Protocol for Elementary School Students in Banyuasin South Sumatera - Yustini Ardillah; Anggun Budiastuti; Dian Safriantini; Rendi Sabana (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Covid-19 continues to increase the number of patients who are positive for Covid-19. Indonesia is a risky country to visit, while the National Data for South Sumatra is the number one province on Sumatra Island with the highest number of Covid-19 patients. Government policy allows regions or regions with yellow zones to open schools offline. Banyuasin Regency is included in the yellow zone of Covid patients, so teaching and learning has been carried out offline with strict implementation of health protocols. To support offline teaching and learning activities, it is necessary to educate students about the 3M movement (maintaining distance, using masks, washing hands with soap). This activity aims to train students to apply the 3M health protocol correctly. The results of the service show that there is an increase in knowledge and changes in student behaviour after receiving training and counselling about health protocols at school. Optimization of health protocols needs to be carried out on an ongoing basis to prevent the transmission of COVID-19 in elementary schools.